2002
DOI: 10.2337/diacare.25.10.1761
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Gestational Diabetes Mellitus and Low Maternal Birth Weight

Abstract: OBJECTIVE -To study the relationship between low birth weight and the presence of gestational diabetes mellitus (GDM) or peripheral insulin resistance during pregnancy.RESEARCH DESIGN AND METHODS -We studied the relationship between peripheral insulin sensitivity (calculated by Matsuda and DeFronzo's oral glucose tolerance test (OGTT)-derived insulin sensitivity index [ISI OGTT ]) or GDM prevalence and birth weight in 604 pregnant women, classified as normally glucose tolerant (n ϭ 462) or affected with GDM (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 19 publications
(13 reference statements)
6
51
0
Order By: Relevance
“…6 For Bangladesh, it seems important to determine the prevalence of GDM for several reasons. Firstly, Bangladeshi women showed higher prevalence of IGT than their male counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…6 For Bangladesh, it seems important to determine the prevalence of GDM for several reasons. Firstly, Bangladeshi women showed higher prevalence of IGT than their male counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, in Italy, Seghieri et al 22 found a significant association between birth weight < 2,600g and gestational diabetes mellitus after adjustment for age, parity, family history of diabetes mellitus and pre-pregnancy BMI. The odds ratio to present gestational diabetes mellitus was nearly two times higher among women with birth weight < 2,600g, when compared to higher birth weights (OR: 1.89; 95%CI: 1.09-3.29).…”
Section: Birth Weightmentioning
confidence: 99%
“…However, the association between maternal diabetes, offspring birth weight and subsequent diabetes is complex because gestational diabetes predisposes to macrosomic infants with higher birth weight (Silverman et al 1991). Women of low birth weight are at increased risk of developing gestational diabetes and type 2 diabetes (Williams et al 1999, Egeland et al 2000, Forsen et al 2000, Innes et al 2002, Seghieri et al 2002 and hence deliver larger babies (Seghieri et al 2002). 'Macrosomic' offspring are themselves at risk of developing obesity (Pettitt et al 1993, Gillman et al 2003, gestational diabetes (Innes et al 2002) and type 2 diabetes later in life (Pettitt et al 1993, Lindsay et al 2000, Catalano et al 2003.…”
Section: Intergenerational Effects On Cardiovascular Risk Factorsmentioning
confidence: 99%